Effects of the SARS-CoV-2 pandemic on women affected by endometriosis: a large cross-sectional online survey. (1st January 2021) - Arena, Alessandro; Orsini, Benedetta; Degli Esposti, Eugenia; Raimondo, Diego; Lenzi, Jacopo; Verrelli, Ludovica; Iodice, Raffaella; Casadio, Paolo; Seracchioli, Renato
Abstract: Introduction: The SARS-CoV-2 pandemic has forced healthcare providers to reorganize their activities to protect the population from infection, postponing or suspending many medical procedures. Patients affected by chronic conditions were among the most affected. In the case of catastrophes, women have a higher lifetime prevalence of post-traumatic stress disorder (PTSD), and those with endometriosis have higher anxiety levels, making them fragile in such circumstances. Materials and methods: In this cross-sectional study, conducted in May 2020, we considered all women aged ≥18 years, followed up at our referral centre for endometriosis. Patients were sent an anonymous 6-section questionnaire via email, containing different validated tools for the evaluation of anxiety levels and the risk of PTSD. A multivariable linear regression was performed to assess the impact of patients' characteristics on the distress caused by the SARS-COV-2 pandemic. Results: Among the 468 women recruited, 68.8% were quite-to-extremely worried about not being able to access gynaecologic care, with almost one-third of them scoring ≥33 on the IES-R. Older age and increased levels of anxiety were associated with higher risks of PTSD (age: b = 0.28, 95% CI = 0.12 − 0.44; GAD-7: b = 1.71, 95% CI = 1.38 − 2.05), with up to 71.8% of patients with severe anxiety (GAD-7 > 15) having an IES-R score ≥33 suggestive for PTSD. Women who could leave home to work showed lower levels of PTSD ( b = −4.79, 95% CI = −8.44 to − 1.15, ref. unemployed women). The implementation of telemedicine in routine clinical practice was favourably viewed by 75.6% of women. Discussion: Women with endometriosis are particularly exposed to the risk of PTSD during the SARS-CoV-2 pandemic, especially if they are older or have higher levels of anxiety. Gynaecologists should resort to additional strategies, and telemedicine could represent a feasible tool to help patients cope with this situation. KEY MESSAGES: The COVID-19 pandemic significantly impacted the lives of women with endometriosis, who appeared to have a considerable risk of PTSD. Older age, higher anxiety levels and unemployment were independently associated with the risk of developing PTSD. Clinicians should develop successful alternative strategies to help patients cope with this situation, and telemedicine might represent an applicable and acceptable solution.